Facebook friendship diplomacy as a bridge to peace: a case study of relations between Libyan and American citizens - Gibson, Lisa (2020)
This thesis develops our understanding of friendship in International Relations by exploring the role of transnational citizen-led Facebook friendship as a form of citizen-led public diplomacy and what these groups tell us about friend and enemy conceptions in International Relations. This case study explores how citizens exercise their agency in redefining identity narratives between states that have a history of conflict by promoting cultural understanding and peaceful relationships through Facebook friendships. This research builds upon the existing literature on friendship in International Relations by conceptualising friendship as a social process between citizens which can improve relations between states and citizens of states. The countries of Libya and America were chosen because of their history of conflict and because Libya is one of the countries subject to President Donald Trump’s travel ban. Face-to-face and Facebook focus group interviews were used to understand how and by what modes of reasoning and narratives Facebook friendships between Libyans and Americans impact Libyans’ views of the American people and American foreign policy. The data was coded using thematic discourse analysis and presented under ten themes: the meaning of friendship; differences between same-culture and cross-cultural friendships; open-mindedness and respect are key; online versus face-to-face friendships; impact of media on views; cultural exchange promotes understanding; trust building and inclusive communication; capacity-building and education programmes; civil society programmes have more impact than government; and US foreign policy is the problem. This research builds upon the existing scholarship in International Relations and Critical Peace and Conflict Studies which challenges state-centric views of the types of actors that have power and agency in International Relations and shows that everyday activities like citizens socialising on Facebook can have political and peace-making purposes. The findings show that the participants in this study see the process of socialising, having dialogue and learning about one another’s culture as a cooperative process of reframing identity narratives and improving relations between their states. This thesis also uses a novel method of Facebook focus groups to collect the data, which made it possible to gain the perspectives of a diversity of Libyans through allowing bilingual answers while also understanding how the participants construct meaning together about the purposes for these Facebook friendships. This thesis argues that the participation in Facebook friendships with Americans does have some impact on Libyans’ views of the American people, but face-to-face exchange programmes have significantly more impact. This research also shows that two-way communication between citizens is seen as the most helpful way to establish trust and that establishing trust is essential to good relations. The findings also suggest that it would be valuable for the US government to focus on facilitating and funding two-way communication and face-to-face exchanges to improve the relations between American and Libyan citizens and improve the way Libyans view America as a whole. However, the US government should also recognise that relations between citizens do not improve Libyans’ views of American foreign policy, because the participants in this study separate their views of the American people from American foreign policy. Instead, it is important for the US government to recognise how years of sanctions against Libya and the current travel ban leave the Libyan people feeling like they are perceived as enemies and how these policies affect their image of the US government and relations between Libya and America.